Postentry Restriction to Human Immunodeficiency Virus-Based Vector Transduction in Human Monocytes - Neil, Stuart (American Society for Microbiology, 2001)
Cells of the monocyte lineage can be infected with human immunodeficiency virus type 1 (HIV-1) both during clinical infection and in vitro. The ability of HIV-1-based vectors to transduce human monocytes, monocyte-derived macrophages, and dendritic cells (DCs) was therefore examined, in order to develop an efficient protocol for antigen gene delivery to human antigen-presenting cells. Freshly isolated monocytes were refractory to HIV-1-based vector transduction but became transducible after in vitro differentiation to mature macrophages. This maturation-dependent transduction was independent of the HIV-1 accessory proteins Vif, Vpr, Vpu, and Nef in the packaging cells and of the central polypurine tract in the vector, and it was also observed with a vesicular stomatitis virus-pseudotyped HIV-1 provirus, defective only in envelope and Nef. The level and extent of reverse transcription of the HIV-1-based vector was similar after infection of immature monocytes and of mature macrophages. However, 2LTR vector circles could not be detected in monocytes, suggesting a block to vector nuclear entry in these cells. Transduction of freshly isolated monocytes exposed to HIV-1-based vector could be rescued by subsequent differentiation into DCs. This rescue was induced by fetal calf serum in the DC culture medium, which promoted vector nuclear entry.